Balancing Industrial Concentration and Competition for Economic Development in Asia: Insights from South Korea, China, India, Indonesia and the Philippines - Mendoza, Ronald Umali; Barcenas, Lai-Lynn Angelica; Mahurkar, Padmini (Journal of Reviews on Global Economics, 2013)
In pursuit of economic growth and development, countries have tried to strike a balance between competition and industrial policies across time. This paper will review the empirical evidence on industrial concentration and its economic correlates (notably firms' performance as measured by profitability, factor productivity and innovation). It will also analyze how the introduction of competition policies and laws in South Korea, China, India, Indonesia and the Philippines affected industrial concentration. It will examine at what point in their industrialization and economic development these economies implemented these laws and policies. The empirical literature suggests that industrial concentration could exhibit an inverted-U-shaped relationship as far as its link to certain economic indicators of success, such as productivity and innovation. This suggests a role for recalibrating policies to adjust the balance between industrial concentration and competition, so that the over-all outcomes are net welfare enhancing. Indeed, country policy experiences reviewed here appear to demonstrate this recalibration, notably following privatization and liberalization policies.